From the Welfare State to the Carceral State: Whither Social Reproduction?. Issue 1 (February 2023) - Abramovitz, Mimi
Historical, feminist scholarship demonstrates that the welfare state underwrote the work of social reproduction, enabling procreation, socialization, sexuality, nurturance, and family maintenance. Carried out by families and other public and private social institutions, social reproduction includes making food, clothing, and shelter available for immediate consumption; ensuring the health and productivity of the current and future labor force; providing for people too old, too young, or too sick to care for themselves; and socializing family members. Historically, social reproduction includes both women's unpaid labor in the home and low-paid labor in the market and converts the wages of paid workers into the means of subsistence for the entire household. The economic crisis of the mid-1970s marked the end of the "golden age" of capitalism, and yielded neoliberal politics that sought to undo the redistributive elements of the New Deal and the Great Society. It called for a smaller state, greater reliance on market forces, and reduced expenditure on family maintenance. This article, a reprint of a 2017 book chapter, explores the crisis in social reproduction in the United States that surfaced with the rise of neoliberalism and the "carceral state."